A Pilot Study on Diabetes Distress, Insulin Growth Factor-I, Insulin-Like Growth Factor Binding Protein-3, and HbA1c in Diabetic Patients - Tahiruddin, Tahiruddin; Indriastuti, Diah; Syahrul, Syahrul; Irwan, Andi Masyitha; Pranata, Satriya (Nurse Media Journal of Nursing, 2025)
Background: Diabetes distress refers to the emotional and psychological burden experienced by individuals in managing their condition, which can influence physiological outcomes and overall well-being. However, the relationship between HbA1c, insulin growth factor-I (IGF-I), and insulin-like growth factor binding protein-3 (IGFBP-3) with diabetes distress in diabetic patients remains elusive.Purpose: The objective of this study was to evaluate the association of IGF-I, IGFBP-3, and HbA1c with diabetes distress in diabetic patients.Methods: A cross-sectional design with purposive sampling was used to recruit subjects from the public health center in Kendari City, Southeast Sulawesi, Indonesia, from May to November 2021. A total of 30 diabetic patients were recruited for the study. Distress data were collected using the Indonesian version of the Diabetes Distress Scale (DDS) questionnaire. HbA1c levels were measured using High-Performance Liquid Chromatography (HPLC). Serum levels of IGF-I and IGFBP-3 were measured using the ELISA (Enzyme-Linked Immunosorbent Assay) kit method. The data were analyzed using regression analysis.Results: Most respondents had moderate distress, with a DDS score of 53.4%, a high IGF-I level of 76.7%, and a low IGFBP-3 level of 76.7%. As many as 60% of respondents had an HbA1c level above 6.4%. IGF-I (ρ-value=0.024) and IGFBP-3 levels (ρ-value=0.042) showed a significant correlation with diabetes distress. However, HbA1c levels did not significantly correlate with diabetes distress (ρ-value=0.155).Conclusion: IGF-I and IGFBP-3 levels were associated with diabetes distress, but HbA1c was not. Patients with higher distress were found to have elevated serum levels of IGF-I and IGFBP-3. Future research should focus on stress management strategies that support efforts to prevent disease and complications associated with diabetes mellitus.